Pengembangan Game “Gemas Si Kakak Gara-Gara Asean” dalam Pembelajaran IPS Kelas VIII di SMP Negeri 2 Gedangsaridi Masa Pandemi - Sri Purwanti; Gunawan Sridiyakmiko (Proceedings Series on Social Sciences & Humanities, 2022)
The COVID-19 pandemic has brought changes in various fields, including the field of education. Learning activities are carried out online, various facilities have been used, but the data shows that there is a decreasing interest and participation of students in participating in online learning, so it takes the creativity of teachers to innovate in order to create learning media that are in accordance with the characteristics of students, with the educational game "Game Si Kakak Gara -gara ASEAN” creates a pleasant atmosphere in social studies learning. This development research aims to develop products and to improve learning outcomes for social studies subjects. The method used is research and development (R&D) which adapts the 4D-Thiagarajan model. The procedure in question includes 4 stages, namely, (1) defining, (2) designing, (3) developing, (4) dissemination (dissemination). The subjects of this study were students of class VIII E of SMP N 2 Gedangsari. The data analysis technique was quantitative-descriptive, in the form of an average expert validation score. The results showed that the feasibility level of the game "Gemas Si Kakak Gara-gara ASEAN" which was developed based on media expert validation was 92.5% for material expert validation; and 91%. As for learning outcomes, the average value of students also increased, before using the game "Game Gemas Si Kakak because of ASEAN" students who reached the KKM were only 20 or 62.5% with an average value of students reaching 68.75 out of 32 students, after using games, students who reach above the KKM become 29 or 90.62% with the average value of students being 84.06 or an increase of 28% from the beginning. This shows that the game "Gemas Si Kakak because of ASEAN" is effective in improving the learning outcomes of class VIII students and is suitable for use as a learning medium.